Prospects of Azotobacter as a Biofertilizer in Saline Soils - Hindersah, Reginawanti; Fitriatin, Betty N; Setiawati, Mieke R; Adawiyah, Aliya Z (JURNAL BUDIDAYA PERTANIAN, 2025)
Climate change causes high waves on the seas that can accelerate the salinization of agricultural land located in coastal areas. Saline soil does not support plant growth because of the limitations of plant roots in absorbing water and nutrients, especially Nitrogen. Increasing salinization causes challenges in finding proper soil management methods, including nature-based solutions. A potential method to strengthen plant growth in saline areas is the introduction of biofertilizers containing nitrogen-fixing bacteria (NFB) that are resistant to salinity. This article aims to review the tolerance of nonsymbolic NFB Azotobacter to salinity and discuss the potential of this beneficial rhizobacterium for mitigating plant cultivation in saline land. The article was compiled through a literature study analyzing various relevant references from national and international journals in the last ten years. Analysis of the references shows that several soil Azotobacter strains are resistant to certain salt levels and have specific physiological characteristics when living in saline environments. Azotobacter induces plant tolerance to high salinity in the pot experiment. Therefore, Azotobacter inoculation becomes one of the alternatives to increase the growth of crops in saline soil.